PERANAN MANAJER LINI DALAM PENGEMBANGAN KARIR KARYAWAN - Marsasi, Endy Gunanto (Universitas Slamet Riyadi, 2004)
ABSTRACT Management and career planning to face the environmental change and organization, which quickly is not easy to. Therefore is needed by design and forming return to develop their career. There are some reason is; why needed by management and good career planning, because career planning become the do it yourself project, entire combination of interest management required by every organizational type have been known better, and people start their career by thinking organization as something that have to be created by â€œ no to be followedâ€. All individual capable to develop the knowledge, skill will place his self in its own career efficacy. In career development, each of individual have to develop the new interest which deal with self management and its career, and also everyone require to learn how to develop the knowledge and adaptation to his self. Career satisfaction is often made by as successfulness indicator program career at one particular organization. Organizational with the high career satisfaction level is indication of how element from organization able to support its employees career development, so that able to trigger the satisfaction appearance in their career. Manager represents one of element from company capable to assist in make-up of satisfaction of employees career. How management support able to influence the career satisfaction will be studied in this research. Cause of interaction between employees and manager will have a share to influence their career satisfaction level. Oftentimes career satisfaction is caused by sympathetic attitude from line manager in supporting the employeesâ€™ career development. Keywords: Career Satisfaction, Management Support, Management Attitude, Line Manager Role